What is attentional refreshing in working memory?. Issue 1 (15th March 2018) - Camos, Valérie; Johnson, Matthew; Loaiza, Vanessa; Portrat, Sophie; Souza, Alessandra; Vergauwe, Evie
Abstract: Working memory is one of the most important topics of research in cognitive psychology. The cognitive revolution that introduced the computer metaphor to describe human cognitive functioning called for this system in charge of the temporary storage of incoming or retrieved information to permit its processing. In the past decades, one particular mechanism of maintenance, attentional refreshing, has attracted an increasing amount of interest in the field of working memory. However, this mechanism remains rather mysterious, and its functioning is conceived in very different ways across the literature. This article presents an up‐to‐date review on attentional refreshing through the joint effort of leading researchers in the domain. It highlights points of agreement and delineates future avenues of research.